Gap-bridging during quasi-simultaneous laser transmission welding - Schmailzl, Anton; Hierl, Stefan; Schmidt, Michael (Physics Procedia, 2016)
Tightness is often the main requirement for quasi-simultaneous laser transmission welds. However, remaining gaps cannot be detected by the used set-path monitoring. By using a pyrometer in combination with a 3D-scanner, weld seam interruptions can be localized precisely while welding, due to temperature deviations along the weld contour. To analyze the temperature signal in correlation to the progress of gap-bridging, T-joint samples with predefined gaps are welded. The set-path is measured synchronously. Additionally, the temperature distribution and the influence of the thermal expansion of the polymers are studied by a thermo-mechanical FEM-process simulation. On top of that, the melt blow-out of the welded samples is analyzed using μCT-measurements. The experiments have shown that closing of a gap can be identified reliably by the temperature signal and that the squeezed melt flow into the gap and the thermal expansion in the gap zone accelerates gap-bridging. Furthermore the inserted heat can be adapted in the fault zone, in order to avoid thermal damage.
Created from Fastlane, Scopus look-up
Keywords: gap bridging; laser transmission welding; process monitoring; pyrometer; quasi-simultaneous welding; temperature measurement